(untitled) (Acta Polytechnica CTU Proceedings, 2017)
This paper deals with the problem of internal rail stress estimation. It is based on a detailed research of contemporary situation in the field, presents basic outlines of the problem and sums up the major research areas and their possible applications in the current state of railway infrastructure management. The directions are divided into four categories in the paper: Displacement Methods, Rail Shifting Methods, Methods Based on Acoustoelastic Effect and Methods Based on Magnetoelastic Effect. Particular methods, both scientific and industrial, are presented in their section respectively. Every method that is presented within the scope of this paper is briefly described and its advantages and disadvantages are mentioned. In the end, potential of application of some of the presented methods in the practical use is discussed.